Estimating the benefit of well-managed protected areas for threatened species conservation - Kearney, Stephen G.; Adams, Vanessa M.; Fuller, Richard A.; Possingham, Hugh P.; Watson, James E. M. (Oryx, 2020)
Protected areas are central to global efforts to prevent species extinctions, with many countries investing heavily in their establishment. Yet the designation of protected areas alone can only abate certain threats to biodiversity. Targeted management within protected areas is often required to achieve fully effective conservation within their boundaries. It remains unclear what combination of protected area designation and management is needed to remove the suite of processes that imperil species. Here, using Australia as a case study, we use a dataset on the pressures facing threatened species to determine the role of protected areas and management in conserving imperilled species. We found that protected areas that are not resourced for threat management could remove one or more threats to 1,185 (76%) species and all threats to very few (n = 51, 3%) species. In contrast, a protected area network that is adequately resourced to manage threatening processes within their boundary could remove one or more threats to almost all species (n = 1,551; c. 100%) and all threats to almost half (n = 740, 48%). However, 815 (52%) species face one or more threats that require coordinated conservation actions that protected areas alone could not remove. This research shows that investing in the continued expansion of Australia's protected area network without providing adequate funding for threat management within and beyond the existing protected area network will benefit few threatened species. These findings highlight that as the international community expands the global protected area network in accordance with the 2020 Strategic Plan for Biodiversity, a greater emphasis on the effectiveness of threat management is needed.